Use of Psoriasis Epidemiology Screening Tool (PEST) to Identify Psoriatic Arthritis in Bosnia and Herzegovina - Petković-Dabić, Jelena; Umičević-Šipka , Sanja; Barišić, Sonja; Dabić, Saša (Scripta Medica, 2025)
Background/Aim: Psoriatic arthritis (PsA) is chronic inflammatory disease with estimated prevalence of 6 % to 41 % in patients with psoriasis. The aim of this study was to determine the prevalence of PsA in Bosnian patients with psoriasis in everyday dermatological practice by using psoriasis epidemiology screening tool (PEST) screening test for detection of PsA.Methods: This cross-sectional study included patients with a confirmed diagnosis of psoriasis. Data on patient demographics, clinical characteristics and treatment history, were collected using a questionnaire. Clinical characteristics of psoriasis included clinical cutaneous manifestations and plaques and psoriasis area and severity index (PASI). The risk of having PsA was evaluated by PEST (scores ≥ 3 indicate risk of PsA). The data were analysed using the Chi-square and Independent t-test. Results: Of 79 included psoriatic patients, 22.8 % had a PEST ≥ 3. Psoriatic patients with PEST ≥ 3 were more likely to have certain comorbidities such as cardiovascular diseases (p = 0.044) and psychological disorders (p = 0.022). The psoriatic patients with PEST < 3 and PEST ≥ 3 did not differ in PASI severity, but psoriatic patients with PEST ≥ 3 were more likely to have nail psoriasis (p < 0.001). Conclusion: In the present study, using PEST questionnaire, one fifth of Bosnian patients were suspected of having PsA, highlighting a need for improved screening for PsA in daily dermatological practice. Earlier care is important because these patients were more likely to have cardiovascular diseases, psychological disorders and nail disease.